MEMANTIK WIRAUSAHA MUDA DI KOTA INDUSTRI (STUDI PERAN PEMERINTAH DAERAH MELALUI PROGRAM WIRAUSAHA MUDA PEMULA DI KABUPATEN BEKASI): - Luki Oka Prastio; Widodo; Selvi Centia; Safaranita Nur Effendi (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
This research is motivated by the government's efforts to minimize the complexity of youth problems such as the lack of participation in the youth workforce, weak entrepreneurial skills, incompatible youth policies at the national and regional levels, and the high rate of youth open unemployment in Bekasi Regency, in addition to a myriad of other social pathologies among youth. This study uses the basis of government role analysis from Diva (2009) consisting of the role of regulator, facilitator and catalyst. The purpose of this study is to analyze the role of the government through the Beginner Young Entrepreneur Program in Bekasi Regency. This research uses qualitative methods, then data collection techniques use literature, observation, interviews. The results of the research show that the government's role through the Beginner Young Entrepreneur Program is not optimal. Viewed based on the role of regulators who have not been able to create a conducive climate, it is manifested from the very small participation quota which is exacerbated by the low interest in entrepreneurship. Based on the role of the facilitator, there is still no access to capital and assistance. Finally, in terms of the role of the catalyst, it is carried out through the provision of knowledge and motivation, but there are deficiencies such as weak empowerment, no awards, and the program's sustainability impact is still questionable.